Preposição de um instrumento para avaliação dos terminais hidroviários de passageiros: estudo de caso no estado do Pará - GARCIA JUNIOR, Guiler Oliveira (Universidade Federal do Pará, 2025)
River transport is the most important means of transport for delivering people and cargo in the State of Pará, and is responsible for promoting the population's quality of life. The region's waterway terminals have very rudimentary logistical planning in terms of their operational dynamics. This brings a lot of inconvenience to those who use the means of transport to travel. The specific purpose of this work was to develop an instrument for evaluating the quality of services offered in passenger terminals in the municipalities of Belém and Salvaterra, in Marajó. Through observational methodology, through the application of evaluative questionnaires from the National Waterway Transport Agency (ANTAQ) and a Survey survey. It was confirmed that the waterway terminals are not operating efficiently and that the factors found, such as lack of security, policing, accessibility, inadequate parking, untrained employees, among others, make operations at port facilities difficult. The results allowed the identification of problems in user access and circulation at waterway terminals, in addition to providing improvements in their infrastructure, accessibility and mobility, directly impacting passengers' quality of life.